2003
DOI: 10.1161/01.atv.0000063109.94810.ee
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perlecan Expression During Vascular Injury

Abstract: Objective-Vascular smooth muscle cells (SMCs), activated by growth factors after arterial injury, migrate and proliferate to expand the intima of the blood vessel. During intimal expansion, proliferation is suppressed and an increasingly large proportion of the neointimal mass is composed of newly synthesized extracellular matrix (ECM). We sough to determine whether the ECM heparan sulfate proteoglycan (HSPG) perlecan, which inhibits SMC proliferation in vitro, also accumulates and limits SMC proliferation dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 61 publications
(77 reference statements)
0
25
0
Order By: Relevance
“…Several previous studies have shown that intact perlecan proteoglycan inhibits in vitro SMC proliferation (6,16,30). An in vivo vascular injury study has shown that perlecan accumulation attenuates neointimal SMC proliferation (11). Moreover, removal of HS from carotid intimal lesions restores the proliferative response of intimal SMCs to PDGF in organ cultures (10).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that intact perlecan proteoglycan inhibits in vitro SMC proliferation (6,16,30). An in vivo vascular injury study has shown that perlecan accumulation attenuates neointimal SMC proliferation (11). Moreover, removal of HS from carotid intimal lesions restores the proliferative response of intimal SMCs to PDGF in organ cultures (10).…”
Section: Discussionmentioning
confidence: 99%
“…Perlecan expression and PTEN activity are associated with developmental and late postinjury decreases in SMC replication. 7,16 PTEN inactivation is associated specifically with actively dividing SMCs during early to mid stages of lesion formation. In the early stages of injury repair, SMCs proliferate in response to increased release of growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, a previous study showed proliferative responses to growth factors of intimal SMCs in late lesions is increased after heparinase treatment. 16 Additionally, heparin increases SMC-derived perlecan core protein production, which may, in turn, promote SMC growth inhibition. 7 However, we have consistently shown heparin or HS chains alone do not elicit the same degree of growth inhibition as fully sulfated perlecan, especially under serumstimulated conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• C (Kinsella et al 2003). Thereafter, they were washed out twice with the extracellular solution and used for patch-clamp experiments.…”
mentioning
confidence: 99%